POTENSI IPAL SKALA INVIDU UNTUK PENGOLAHAN LIMBAH CAIR INDUSTRI BATIK DI PEKALONGAN - Bambang Priadie (Jurnal Dinamika Penelitian Industri, 2017)
The purpose of this study was to determine the efficiency of individual scale of WWTP  batik in reducing wastewater batik pollutants through coagulation, flocculation, and filtration.Chemicals used in the study include: sulfuric acid, lime, aluminium formulated chloride, polymers, zeolites and activated charcoal. Making this  batik WWTP individual scale is easy to do because of construction materials such as plastic drums is “used storage of chemicals” and  easily obtainable in the market. WWTP individual scale of batik potentially use to increase capacity of the existing communal because it can reduce levels of pollutants BOD, COD, TSS, and oils and fats so that the wastewater processed does not exceed the effluent quality standards. Potential application of the WWTP batik individual scale can be applied on a batik’s home-industry scale or small and medium enterprises (SMEs)